Clinical contraception in a rural NGO area in Bangladesh : findings of a baseline study - Sobhan, Farzana; Islam, Ariful; Khan, Md. Shamsul Islam; International Centre for Diarrhoeal Disease Research, Bangladesh; Operations Research Project (International Centre for Diarrhoeal Disease Research, Bangladesh) (Dhaka : ICDDR,B, Centre for Health and Population Research, 2000)
Case study of Chagalnaiya upazila, Feni district, Bangladesh.
Includes bibliographical references.
Keywords: Contraceptives -- Bangladesh -- Chagolnaiya Upazila -- Case studies